Analysis of Islamic Law Compilation on Application for Child Marriage Dispensation - Sutisna; Umi Habibah; Rudi Hartono (Technium Education and Humanities, 2024)
Religious Courts can grant relief to prospective brides who are not old enough to hold a marriage based on Marriage Law Number 16 of 2019. This includes men and women who have not reached the age of 19. This study aims to find a review of the IHL regarding judges’ considerations when granting dispensation for underage marriage. The study also looked at what judges at the Cibinong Religious Court consider when they grant dispensation for underage marriage. The study used qualitative methodology. Data collection is done through observation, interviews, and documentation. The results showed that, based on the IHL Review and its findings, the IHL serves as a legal basis to allow marriage dispensation in Law Number 16 of 2019 concerning marriage, where article 7 paragraph (2) and paragraph (4) stipulate that the minimum age of prospective men and women is 19 years. In addition, the IHL serves as a review of judges’ deliberations when they decide to apply marriage dispensation.